Menstrual cycle affects iron homeostasis and hepcidin following interval running exercise in endurance-trained women - Alfaro-Magallanes, V. M.; Barba-Moreno, L.; Romero-Parra, N.; Rael, B.; Benito, P. J.; Swinkels, D. W.; Laarakkers, C. M.; Díaz, A. E.; Peinado, A. B. (European Journal of Applied Physiology, 2022)
Purpose Menstrual cycle phase affects resting hepcidin levels, but such effects on the hepcidin response to exercise are still unclear. Thus, we investigated the hepcidin response to running during three different menstrual cycle phases.